Factors that Influence the EmployeePerformance - Arfandy Dinsar; Irawati Nur (www.amertainstitute.com, 2023)
This study emphasizes the factors of career development and work experience, because these cannot be separated from employee performance which can support the achievement of the organization as a whole. The objectives of this study are as follows: 1). To analyze career developmenton the performance of employees at the Regional Financial Board of the City of Parepare (2) To analyze work experience on the performance of employees at the Regional Financial Board of the City of Parepare. 3). To analyze career development and work experience on employee performance at the Regional Financial Board of the City of Parepare. This research uses quantitative and qualitative methods. The data analysis method used is multiple linear regression analysis and sampling using probability sampling. In this study, the sample used was 77 employees of the Parepare City Regional Finance Agency. The results of the study are as follows: (1). the career development variable (X1) is 0.438 with atcount of 3.588 > from a ttable of 1.992 and a significance of 0.05 (sig.= 0.001 <0.05). (2). the work experience variable (X2) is 0.433 with tcount 3.545 > from ttable 3.545 and a significance of 0.05 (sig.=<0.05). (3). career development variables (X1) and work experience (X2) together influence employee performance variables (Y) where Fcount > Ftable 65.590 > 3,12.